COVID-19 pandemic; transmembrane protease serine 2 (TMPRSS2) inhibitors as potential drugs. - Jankun, Jerzy (Translation: The University of Toledo Journal of Medical Sciences, 2020)
Ongoing search for treatment to ease COVID-19 pandemic concentrate on development of a vaccine or medication to prevent and treat this disease. One of the possibilities is developing new antiviral drugs that are aiming at both a virus replication or the host factor(s) that are critical to virus’s replication. Serine proteases, which activate the viral spike glycoproteins and facilitate virus-cell membrane fusions for host cell entry, its replication and spread, are proposed as the potential targets for antiviral drug design. Existing literature is already providing evidence that transmembrane protease serine 2 (TMPRSS2) is one of the promising targets. When inhibited it can slow or stop replication of viruses including severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). One of the convincing evidences of the critical role of TMPRSS2 in the coronavirus’s replication was provided by animal study. The replication of influenza viruses was inhibited in TMPRSS2(-/-) knockout mice in comparison to wild type (WT) mice, which developed high mortality rate. Existing inhibitors of TMPRSS2 can be divided into two groups. The first include drugs already approved by FDA or other organizations for treatment of different diseases. That include: Camostat (from Japan, produced by Ono Pharmaceutical), aprotinin (Trasylol, produced by Nordic Group Pharmaceuticals) and rimantadine (Flumadine, produced by Forest Pharmaceuticals, Inc.). Existing in vitro, in vivo and some limited human studies show that this type of drugs limit reproduction of coronaviruses and/or prevented the development of viral pneumonia. One study indicated that combined treatment by aprotinin and rimantadine prevented the development of fatal hemorrhagic viral pneumonia, and protected about 75% animals, when the separate administration of aprotinin or rimantadine induced less protection. The second group includes potential drugs not approved for the human use yet. That include plasminogen activator inhibitor type 1 (PAI-1) and recently developed small molecular inhibitors. PAI-1 is a serine protease inhibitor that regulates physiological breakdown of blood clots by inhibiting of tissue (tPA) and urokinase (uPA) plasminogen activators. But PAI-1 is also an effective inhibitor of various membrane-anchored serine proteases including TMPRSS2. It was reported that PAI-1 inhibited trypsin- and TMPRSS2-mediated cleavage of hemagglutinin and suppressed influenza virus in animals. PAI-1 is human in origin and engineered forms with extended half-life were developed and could be an attractive addition to the existing TMPRSS2 inhibitors. And finally, derivatives of sulfonylated 3-amindinophenylalanylamide were found to inhibit TMPRSS2 with a high affinity and efficiently block the influenza virus propagation in human cells. This paper is intended to provide review on possible or hypothetical beneficial effects of (TMPRSS2) inhibitors as one of options to fight infection with Covid-19.